Deletion of GPR30 Drives the Activation of Mitochondrial Uncoupling Respiration to Induce Adipose Thermogenesis in Female Mice - Luo, Jing; Wang, Yao; Gilbert, Elizabeth; Liu, Dongmin (Frontiers in Endocrinology, 2022)
Thermogenic adipocytes possess a promising approach to combat obesity with its capability promoting energy metabolism. We previously discovered that deletion of GPR30 (GPRKO), a presumably membrane-associated estrogen receptor, protected female mice from developing obesity, glucose intolerance, and insulin resistance when challenged with a high-fat diet (HFD). In vivo, the metabolic phenotype of wild type (WT) and GPRKO female mice were measured weekly. Acute cold tolerance test was performed. Ex vivo, mitochondrial respiration of brown adipose tissue (BAT) was analyzed from diet-induced obese female mice of both genotypes. In vitro, stromal vascular fractions (SVF) were isolated for beige adipocyte differentiation to investigate the role of GPR30 in thermogenic adipocyte. Deletion of GPR30 protects female mice from hypothermia and the mitochondria in BAT are highly energetic in GPRKO animals while the WT mitochondria remain in a relatively quiescent stage. Consistently, GPR30 deficiency enhances beige adipocyte differentiation in white adipose tissue (WAT) and activates the thermogenic browning of subcutaneous WAT due to up-regulation of UCP-1, which thereby protects female mice from HFD-induced obesity. GPR30 is a negative regulator of thermogenesis, which at least partially contributes to the reduced adiposity in the GPRKO female mice. Our findings provide insight into the mechanism by which GPR30 regulates fat metabolism and adiposity in female mice exposed to excess calories. These findings reveal a novel role of GPR30 in the control of thermogenesis and energy expenditure in females and may be instrumental in the development of new therapeutic strategies for obesity.